The Role of APOA-I in Alzheimer’s Disease: Bridging Peripheral Tissues and the Central Nervous System - Guanfeng Xie; Gege Jiang; Liqin Huang; Shangqi Sun; Yuwei Wan; Fang Li; Bingjie Wu; Ying Zhang; Xiaoyi Li; Bingwan Xiong; Jing Xiong (Pharmaceuticals)
Lipid metabolism disorders represent a significant risk factor for the pathogenesis of Alzheimer’s disease (AD). Apolipoprotein E (APOE) has been regarded as a pivotal regulator of lipid homeostasis in the central nervous system (CNS), with polymorphic alleles identified as genetic risk factors for late-onset AD. Despite advances in APOE research and the development of numerous pharmaceutical approaches targeting distinct APOE isoforms, there remain limited treatment approaches for AD that focus on lipid metabolic homeostasis. Consequently, it is necessary to reevaluate the lipid metabolic process in the CNS. Apolipoprotein A1 (APOA-I), a major component of high-density lipoprotein (HDL), plays a crucial role in reverse cholesterol transport from tissues to the liver to maintain lipid homeostasis. Over the past few decades, numerous studies have suggested a connection between reduced APOA-I levels and a higher risk of AD. APOA-I is synthesized exclusively in the liver and intestines, and there is a lack of conclusive evidence supporting its functional significance within the central nervous system, in contrast to APOE, which is produced locally by glial cells and neurons within the CNS. Moreover, APOA-I’s ability to penetrate the blood-brain barrier (BBB) is still poorly understood, which causes its significance in central lipid metabolism and AD pathophysiology to be mainly disregarded. Recent advancements in tracing methodologies have underscored the essential role of APOA-I in regulating lipid metabolism in the CNS. This review aims to elucidate the physiological functions and metabolic pathways of APOA-I, integrating its associations with AD-related pathologies, risk factors, and potential therapeutic targets. Through this discourse, we aim to provide novel insights into the intricate relationship between AD and APOA-I, paving the way for future research in this field.